ANALISIS EKONOMI POLITIK KEBIJAKAN PEMBANGUNAN TOL TANGGUL LAUT SEMARANG-DEMAK DI KECAMATAN SAYUNG KABUPATEN DEMAK - Jessica Xena Boru Namora; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The construction of Tol Tanggul Laut Semarang-Demak (TTLSD) as a National Strategic Project (PSN) valued at Rp15.3 trillion contains tensions between the narrative of rob flood mitigation and larger economic-political interests. This study analyzes the implementation of TTLSD as a political-economic arena, examines policy priorities, and investigates the socio economic impacts on the coastal communities of Desa Bedono and Desa Sriwulan, Sayung Subdistrict, Demak Regency. Employing a qualitative case study approach, data were collected through in-depth interviews with seven purposively selected informants, including government officials, WALHI activists, village heads, and affected residents. The analysis draws on Rachbini’s (1996) political economy theory, Harvey’s (2003) accumulation by dispossession, and Jessop’s (2016) state capitalism. The findings indicate that TTLSD implementation is highly centralized, prioritizing industrial zones and investors through the “vanished land” mechanism and inadequate compensation. Coastal communities experience multilayered marginalization, including livelihood destruction, social fragmentation, and loss of local knowledge. This study recommends more inclusive policy processes, fairer compensation mechanisms, and greater recognition of local ecological knowledge in future PSN projects.